Blended Learning: An Effective Approach for Online Teaching and Learning - Bhadri, Gururaj N.; Patil, Laxmikant R. (Journal of Engineering Education Transformations, 2022)
The present education system has been disturbed due the COVID-19 pandemic and has imposed a greater challenge on educational institutions to seek out alternative approaches in the teaching-learning process. Most of the educational institutions took several initiatives to impart education with the aid of digital technology. In Today’s world knowledge construction in students can be enhanced by combining technology with the traditional way of lecture delivery. Blended learning is a technique which integrates digital media and technology along with traditional classroom activity. It also provides more flexibility for students to customize their learning experiences. Both online and offline will complement each other by using their individual strength. This paper presents a Blended learning approach using Modular Object-Oriented Dynamic Learning Environment (Moodle) as Learning Management System (LMS) platform. Asynchronous videos were created in studios using Lightboard and uploaded on LMS and subsequent Synchronous classes were handled using the MS Teams platform. Learners Centric Blended learning model includes interactive videos, Frequently Asked Questions (FAQs), post-tests, additional study materials, Quizzes, Assignment submissions, etc. This model is effectively implemented for all the courses in our institution and is illustrated in this paper using the Numerical Methods and Differential Equations (NMDE) course at second Year Biotechnology. An online survey was conducted to understand the perception of the students about the blended learning approach through LMS. The results of feedback revealed that the blended learning approach is more flexible and provides independent opportunities for students to learn. More than 82% of the students have given positive feedback towards this technological transformation in teaching and learning.